Influence of Sintering Temperature on Low-field Spin-polarized Tunneling Magnetoresistance of La0.7Ca0.3MnO3 - Phong, Pham Thanh; Manh, Do Hung; Hong, Le Van; Phuc, Nguyen Xuan; Khiem, Nguyen Van; Hung, Vu Van (Communications in Physics, 2008)
In this study we report the effect of sintering temperature on the low field magnetoresistance(LFMR) of La0.7Ca0.3MnO3 manganite synthesized through sol-gel technique. TheLa0.7Ca0.3MnO3 has been sintered at 600°C, 700°C, 800°C, 900°C and 1200°C. The crystalliteas well as particle size also show strong dependence on the sintering temperature. Whilethe ferromagnetic – paramagnetic (FM-PM) transition temperature remains almost constant,the metal – insulation transition temperature drop gradual and the low field magnetoresistance(LFMR) increase with a decrease in grain size. We have analyzed our data based on the spin –polarized transport of conduction electrons at the grain boundaries.